Contextual Effect of Village on the Risk of Pneumonia in Children Under Five in Magetan, East Java - Yola Alqorien Mustikarani; Setyo Sri Rahardjo; Isna Qadridjati; Hanung Prasetya (Journal of Epidemiology and Public Health, 2019)
Background: Pneumonia is a major cause of illness and death in children under five worldwide. Studies into the contextual effect of village are lacking in Indonesia. This study aimed to determine contextual effect of village on the risk of pneumonia in children under five in Magetan, East Java.Subjects and Method: This was a case control study conducted in Magetan, East Java, from October 2018 to December 2018. A sample of 225 children under five from 25 villages was selected by fixed disease sampling. The dependent variable was pneumonia. The independent variables were nutritional status, vitamin A intake, maternal stress, maternal education, family income, family smoking, cooking fuel, house physical environment, and the presence of children in the kitchen when cooking. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: Maternal stress (b= 1.91; 95% CI= 0.75 to 3.06; p= 0.001), family smoking habits (b = 1.39; 95% CI = 0.46 to 2.32; p = 0.003), cooking fuel (b= 1.51; 95% CI= 0.46 to 2.55; p= 0.005), and the presence of children in the kitchen when cooking (b= 1.37; 95% CI = 0.38 to 2.35; p= 0.007) increased the risk of pneumonia in children under five. The risk of pneumonia was reduced by good nutritional status (b= -1.74; 95% CI= -2.70 to -0.78; p <0.001), complete vitamin A status (b= -1.14; 95% CI= -2.04 to -0.24; p= 0.013), high maternal education (b= -1.41; 95% CI= -2.45 to -0.37; p= 0.008), high family income (b= -0.91; 95% CI= -1.80 to -0.02; p= 0.045), and healthy home physical environment (b= -1.86; 95% CI= -3.20 to -0.52; p= 0.007). Village had a strong contextual effect on pneumonia among children under five with ICC= 21.32%.Conclusions: Maternal stress, family smoking habits, cooking fuel, and the presence of children in the kitchen when cooking increase the risk of pneumonia in children under five. It is reduced by good nutritional status, complete vitamin A status, high maternal education, high family income, and healthy home physical environment. Village has a strong contextual effect on pneumonia among children under fiveKeywords: pneumonia, children under five, biopsychosocial, environmental, determinants, multilevel analysisCorrespondence: